The Future Landscape of Endothelial Cells Research in Psoriasis: Bibliometric Analysis and Literature Review - Long SY; Shang L; Shi H; Zhao S; Cao J; He Y (Dove Medical Press, 2023)
Si-Yu Long,* Lin Shang,* Huijuan Shi, Siqi Zhao, Jiali Cao, Yanling He Department of Dermatology, Beijing Chao-Yang Hospital, Capital Medical University, National Clinical Research Center for Skin and Immune Diseases, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiali Cao; Yanling He, Department of Dermatology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 10020, People's Republic of China, Email cnsk2008@126.com; hylchaoyang@163.comBackground: Psoriasis is a global health concern as a chronic inflammatory skin disease. Endothelial dysfunction has been implicated in psoriasis pathogenesis.Objective: This study aims to explore the scientific literature on the relationship between psoriasis and endothelial cells using bibliometric analysis, identifying research trends and public interest in this topic.Methods: We analyzed articles on the topic of endothelial cells and psoriasis in the Web of Science (WoS) Core Collection from 1987 to 2022, examining their distribution by publication year, country, organization, author, and journal. We used bibliometric software, including CiteSpace and R package bibliometrix, to visualize co-authorship relations, keyword citation burst analysis, co citation networks, keyword time zone map, burst references and cluster analysis.Results: Our analysis included 993 publications. The bibliometric analysis revealed a steady increase in the number of publications on psoriasis and endothelial cells over the past decade. The United States was the leading contributor to this field. The Journal of Investigative Dermatology was the most high-yield publication journal. Burst references analysis identified key articles that have significantly influenced the field, including studies on the role of endothelial dysfunction in psoriasis pathogenesis and the association between psoriasis severity and cardiovascular outcomes. 9 clusters were grouped in the key-word citation network. "Expression", "inflammation", "endothelial growth factor" and "angiogenesis" were the research focuses, while "cardiovascular disease", "atherosclerosis", "endothelial dysfunction", and "oxidative stress" might be the future research hotspots.Conclusion: This bibliometric analysis sheds light on the growing acknowledgement of the involvement of endothelial cells in psoriasis, with the United States taking the lead. It also emphasizes the necessity for additional research to unravel the underlying mechanisms connecting psoriasis, endothelial dysfunction, and cardiovascular comorbidities. Ultimately, this research will contribute to the development of enhanced management strategies for psoriasis patients.Keywords: bibliometric analysis, endothelial cells, psoriasis, inflammation, cardiovascular risk, molecular mechanisms